PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDIDIKAN KARAKTER MATERI MITIGASI BENCANAKELAS XI IPS DI SMA NEGERI 1 AMANUBAN TENGAH - Luhamiha, Linda; Rahmawati, Arfita; Sunimbar, Sunimbar (Jurnal Geografi, 2023)
Student worksheets based on character education used for learning effectiveness on natural disaster mitigation materials at SMA Negeri 1 Amanuban Tengah. The method used in this research (Research and Development) which consists of Define (defining), Design (planning) Develop (development), Dissemminate (Deployment). The trials in this study amounted to 25 students. The instruments used are material expert validation instruments, media expert instruments, student response questionnaires, teacher response questionnaires and learning outcomes tests. The results of this study are as follow: 1) based on the results of validation by material experts obtained an average of 87% with very valid criteria and validation results by media experts obtained an average of 86% with very valid criteria 2) based on the results of students responses obtained an average an average of 80% with practical criteria and the teacher’s responses results obtained an average of 86% with very practical categories 3) based on the learning outcomes test before using the LKPD an average of 40% was obtained with less effective and after using the LKPD an average of 80% obtained with effective criteria.